Sustainable development in the Cameron Highlands, Malaysia - Barrow, C.J,; Clifton, J.,; Chan, N.W,; Tan, Y.L., (Environmental Management Society, Malaysia, 2005)
This paper examines the progress and prospects for sustainable development in the Cameron Highlands, Peninsular Malaysia, focusing especially on agriculture. Vegetable, flower and fruit production in the Highlands have caused extensive forest clearance and the excavation of valley sides and floors. This causes loss of biodiversity, unstable ground that is liable to landslide, soil erosion and agrochemical pollution of streams. Unsustainable agriculture has severe impacts on the Cameron Highlands environment, wildlife, tourism, and local people’s well being, and its effects are felt further afield, especially through the degradation of quality and quantity of water supplies which flow to surrounding lowlands. The silting of streams and reservoirs also increases the risk of flood damage. Because impacts will be felt across broad swathes of the lowlands it is in the interests of the federal government and surrounding states to invest in Cameron Highlands improvements. The new highway from Ipoh, opened in 2003, is likely to prompt further horticultural development in once remote parts of the Cameron Highlands. There are opportunities to develop sustainable agriculture and to integrate it with tourism development and the improvement of local people’s livelihoods, including indigenous peoples. These opportunities should be grasped before it is too late